Livelihood Improvement through Hybrid Vegetable Cultivation - Mathur, I. J.; Intodia, S. K.; Agarwal, S. K. (Indian Farming, 2015)
There are a number of tribal households in the South Rajasthan region which have benefitted because of the livelihood security interventions introduced under NAIP. Initiative has been taken to improve and ensure livelihood of small and marginal farmers of tribal dominated areas through diversification of existing cropping system with high value crops.